Ethical reflection: The palliative care ethos and patients who refuse information - Joar Björk (Palliative Care and Social Practice)
Situations wherein a patient refuses potentially important information present tricky ethical challenges for palliative care staff. This critical essay looks to both mainstream bioethics and the palliative care ethos for recommendations on whether or not to provide information in such situations. Such cases highlight controversies surrounding autonomy within mainstream bioethics, making the latter an unlikely source of clear and coherent guidance on this specific topic. The palliative care ethos, as presented by authors within the palliative care community claiming to (re)present such an ethos, may be a more promising source for practical and ethical recommendations. Eleven aspects of the palliative care ethos that may be relevant for such situations are presented, and their implications, individually and collectively, are summarised. Taken as a whole, the palliative care ethos seems to recommend a strategy of using communication skills and time to try to get information across to the patient without forcing things. The recommendation is nuanced and highly contextualised, which increases its validity for clinical practice. Some meta-ethical questions are discussed regarding the use of the palliative care ethos as a source of guidance in ethically challenging clinical situations. All in all, probing the palliative care ethos for practical guidance is an interesting possibility that deserves further ethical and practical reflection.